The impact of public art on tourism and community engagement in Pekan Parit, Perak - Sazali, Muhamad Ferdhaus; ., Nur Ayunni (2025)
This study explores the role of public art in promoting tourism and community engagement in Pekan Parit, Perak, a small Malaysian town with a rich cultural heritage. Public art, encompassing murals, sculptures, and installations, offers an avenue for preserving cultural identity, enhancing urban aesthetics, and revitalizing local economies. However, challenges in maintenance, community participation, and sustainable integration hinder its full potential. This mixed-methods research investigates the current state of public art in Pekan Parit, its impact on residents and tourists, and the potential for improved engagement and conservation. We collected data through surveys with 103 residents, supplemented by site observations to assess awareness, perceptions, and preferences regarding public art initiatives. Despite the widespread recognition and value of public art for its aesthetic and cultural significance, challenges arise due to maintenance issues and limited public involvement. The study emphasizes the need for structured public art master planning that includes diverse stakeholders, ensuring that art installations contribute to both cultural preservation and tourism development. Recommendations include establishing maintenance protocols and promoting public art as a tool for community pride and identity, creating an integrated approach to heritage conservation and urban development in Pekan Parit.